Peran Pemerintah Kabupaten Kudus dalam Pemberdayaan Ekonomi Masyarakat melalui SIDUKU Perspektif Maqashid Syariah - Aulia, Rahma (Sharia Faculty Islamic Economic Law Study Department, 2022)
This study aims to determine the role of Kudus regency government regarding innovation to support the people's economy improvement during the COVID-19 pandemic by combining it with developing technology. This research used empirical methods by looking at legal facts and the law process in society. Empirical legal research prioritizes primary data by using data collection techniques through observation and interviews. The results of this study indicate that the innovation developed by the Government of Kudus Regency, SIDUKU, is a website-based application for collecting MSME data in Kudus Regency which can find out the distribution and type of business to facilitate data collection on MSME in Kudus. The concept of innovation developed by the Regional Government of Kudus Regency, especially the Office of Manpower, Industry, Cooperatives and SMEs, is certainly in line with Maqashid Syariah in terms of maintaining life and property which can be one of economic solutions during the pandemic.